Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1988
DOI: 10.1083/jcb.107.5.1881
|View full text |Cite
|
Sign up to set email alerts
|

The function of multiple extracellular matrix receptors in mediating cell adhesion to extracellular matrix: preparation of monoclonal antibodies to the fibronectin receptor that specifically inhibit cell adhesion to fibronectin and react with platelet glycoproteins Ic-IIa.

Abstract: Abstract. We have identified monoclonal antibodies that inhibit human cell adhesion to collagen (P1H5), fibronectin (P1F8 or P1D6), and collagen and fibronectin (P1B5) that react with a family of structurally similar glycoproteins referred to as extracellular matrix receptors (ECMRs) II, VI, and I, respectively. Each member of this family contains a unique ¢t subunit, recognized by the antibodies, and a common [~ subunit, each of ~140 kD. We show here that ECMR VI is identical to the fibronectin receptor (FNR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
205
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(211 citation statements)
references
References 38 publications
5
205
0
1
Order By: Relevance
“…Figure 5A and B demonstrate clearly that pancreatic cancer cell adhesion and migration on type I collagen is mediated exclusively by the a 2 b 1 integrin, and that neither the a 1 , a 3 , a 5 , or a 6 integrin subunits, nor the a v b 3 or a v b 5 integrins appear to be involved in the adhesive interactions between AsPC-1, BxPC-3, CFPAC, or FG pancreatic cancer cells and type I collagen. Immunoprecipitation studies shown in Figure 4 and previous studies by us and other laboratories (Cheresh and Spiro, 1987;Wayner and Carter, 1987;Sonnenberg et al, 1988;Wayner et al, 1988Wayner et al, , 1993Grzesiak et al, 1992Grzesiak et al, , 2005aFabbri et al, 1996) demonstrate that the monoclonal antibodies used for the type I collagen inhibition studies are functional.…”
Section: Type I Collagen Promotes Maximal Haptokinetic Cell Migrationsupporting
confidence: 57%
See 1 more Smart Citation
“…Figure 5A and B demonstrate clearly that pancreatic cancer cell adhesion and migration on type I collagen is mediated exclusively by the a 2 b 1 integrin, and that neither the a 1 , a 3 , a 5 , or a 6 integrin subunits, nor the a v b 3 or a v b 5 integrins appear to be involved in the adhesive interactions between AsPC-1, BxPC-3, CFPAC, or FG pancreatic cancer cells and type I collagen. Immunoprecipitation studies shown in Figure 4 and previous studies by us and other laboratories (Cheresh and Spiro, 1987;Wayner and Carter, 1987;Sonnenberg et al, 1988;Wayner et al, 1988Wayner et al, , 1993Grzesiak et al, 1992Grzesiak et al, , 2005aFabbri et al, 1996) demonstrate that the monoclonal antibodies used for the type I collagen inhibition studies are functional.…”
Section: Type I Collagen Promotes Maximal Haptokinetic Cell Migrationsupporting
confidence: 57%
“…The function-blocking monoclonal antibodies directed against particular integrin subunits and integrins used in these studies have been described (Cheresh and Spiro, 1987;Wayner and Carter, 1987;Sonnenberg et al, 1988;Wayner et al, 1988Wayner et al, , 1993Fabbri et al, 1996), and include FB12 (a 1 ), P1E6 (a 2 ), P1B5 (a 3 ), P1D6 (a 5 ), GoH3 (a 6 ), P5D2 (b 1 ), LM609 (a v b 3 ), P1F6 (a v b 5 ), and ASC-3 (b 4 ) (Chemicon International, Temecula, CA, USA). For immunoprecipitation (IP) experiments, we used the monoclonal antibodies described above along with rabbit polyclonal antisera against the a 5 integrin subunit, which has also been described previously (Ruoslahti and Pierschbacher, 1987).…”
Section: Antibodiesmentioning
confidence: 99%
“…The as and a, subunits combine with PI to form receptors for fibronectin (36) and laminin (37), respectively. The as subunit is a 135-kd protein; the a, subunit is a 120-kd protein.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble ligand or antibody to alpha5beta1 may displace this inhibitory substance, allowing normal signal transduction to occur. A central role of alpha5beta1 in growth control may explain why diverse transforming agents have been found to affect the structure, expression, or function of this particular integrin (Hirst eta/., 1986;Plantefaber and Hynes, 1989;Symington et al, 1989 (Hemler et a/, 1987;Wayner and Carter, 1987;Wayner et al, 1988). Monoclonal antibodies to the platelet glycoproteins (anti-llbill.…”
Section: Selection Of Fa-k562mentioning
confidence: 99%